The Contribution of Literature in the Humanization of the Law in Indonesia - Tatit Hariyanti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
Law and Literature movement has been developing in western countries since the first half of the twentieth century as the response of the isolation of law from other disciplines and the idea of humanizing law to have optimal function for the betterment of social order. This movement exerts great potentials in developing methods of teaching and interpreting legal texts resulting in the betterment of the performance of the law makers and the deeper understanding of law. The isolation also happens in Indonesia; however, there is not obvious echo of the movement in Indonesia. There is no place of literature in Indonesians law. Under the movement of law and literature, this qualitative research aims not at finding out the reason of excluding literature from law; instead it aims at demontrating and promoting that literature could give contribution in understanding and producing humanistic legal texts in Indonesia. Taking available data by heuristic model and comparative and descriptive analysis, this research concludes that literary works could provide sources of learning and understanding law, and literary theories could be applied in improving the making of more humanistic legal texts in Indonesia.